Penguatan Penyusunan Soal AKM Sekolah Dasar Bagi Guru Di SD Negeri Inpres Skouw Mabo Perbatasan RI-PNG - Elieser Kulimbang; Rian Efendi; Dian Septikasari (Jurnal PKM: Karya dan Inovasi untuk Negeri, 2026)
This community service activity aims to strengthen the competence of elementary school teachers in developing numeracy questions oriented towards the Minimum Competency Assessment (AKM) through practice-based mentoring and local context. The program was implemented at SD Negeri Inpres Skouw Mabo, in the Indonesia-PNG border region, using a direct participatory approach involving all teachers. The activity stages included initial observations, presentation of AKM concept material, a question development workshop, revision mentoring, and evaluation of results. Data were collected through interviews, process observations, and analysis of the quality of the question products before and after the mentoring. The results showed an increase in teachers' understanding of the characteristics of AKM, particularly in the development of contextual stimuli, the selection of numeracy content, and the determination of cognitive levels based on reasoning. Teachers who previously tended to develop procedural questions without context were able, after mentoring, to design questions based on real-life situations of students in Papua, such as local social and cultural activities. The iterative revision process helped teachers understand that the strength of AKM questions lies in their ability to encourage students to read, understand information, and reason before answering. This activity not only improved teachers' technical skills in developing questions but also built their confidence as agents of change in numeracy literacy learning in the border region. This mentoring model has proven to be effective and worthy of replication in schools in 3T areas as an effort to equalize the quality of education and strengthen the implementation of the National Assessment at the educational unit level.